A Breast Cancer Polygenic Risk Score Validation in 15,490 Brazilians Using Exome Sequencing - Flávia Eichemberger Rius; Rodrigo Santa Cruz Guindalini; Danilo Viana; Júlia Salomão; Laila Gallo; Renata Freitas; Cláudia Bertolacini; Lucas Taniguti; Danilo Imparato; Flávia Antunes; Gabriel Sousa; Renan Achjian; et al. (Diagnostics)
Background/Objectives: Brazil has a highly admixed population. Polygenic risk scores (PRSs) have mostly been developed from European population studies, and their application to other populations is challenging. To assess the use of PRS for breast cancer (BC) risk in Brazil, we evaluated four PRSs in the Brazilian population. Methods: We analyzed a Brazilian cohort composed of 6206 women with a history of breast cancer and 8878 unphenotyped adults as controls. Genomic variants were imputed from exomes, and scores were calculated for all samples. Results: After individuals with known pathogenic or likely pathogenic variants in BRCA1, BRCA2, PALB2, PTEN, or TP53 genes, and first-degree relatives of the probands were excluded, 5598 cases and 8767 controls remained. Four PRS models were compared, and PRS3820 achieved the best performance, with an odds ratio (OR) of 1.43 per standard deviation increase (p value < 0.001) and an OR of 1.88 (p value < 0.001) for the top decile. PRS3820 also performed well for different ancestry groups: East Asian majority (OR 1.59, p value 0.004), Non-European majority (OR 1.45, p value < 0.001), and European majority (OR 1.43, p value < 0.001). Conclusions: Among the different PRSs, PRS313 and PRS3820 could be validated in our Brazilian cohort, with the latter exhibiting the best performance. While further clinical studies are necessary to guide clinical practice, this work represents an important step toward improving BC precision medicine in Brazil.